2009
DOI: 10.17221/98/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the content of neuropeptides in intestinal lymph nodes of pigs suffering from experimental Brachyspira hyodysenteriae infection

Abstract: ABSTRACT:The studies were performed in order to investigate the mutual interrelationship of the peripheral nervous system and particular types and sub-types of lymphocytes located in the intestinal lymph nodes of the pig. Using the ELISA method and the flow cytometry the tissue concentration of VIP, SP, GAL and SOM, as well as the number of lymphocytes containing antigens CD2, CD21, CD4, CD5, CD8 and TCRgamma/delta were determined. As compared to 4-months old pigs of the control group, in 4-months old pigs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…An indispensable role of the galanin system in immune regulation has been underpinned by several in vitro and in vivo studies. For example, high amounts of galanin were found in porcine lymphoid organs 23 . Furthermore, galanin is produced in peripheral tissues such as the skin during inflammation 24 .…”
Section: Introductionmentioning
confidence: 99%
“…An indispensable role of the galanin system in immune regulation has been underpinned by several in vitro and in vivo studies. For example, high amounts of galanin were found in porcine lymphoid organs 23 . Furthermore, galanin is produced in peripheral tissues such as the skin during inflammation 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The ENS may undergo changes under the influence of various physiological and pathological stimuli such as aging, diet, inflammatory processes and other diseases (Gonkowski et al 2003, Vasina et al 2006, Gonkowski and Całka 2012. Lakomy et al (2009) and Kaleczyc et al (2010) demonstrated that cytokine expression in Peyer's patches and the correlations between the ENS and the immune system of the digestive tract can change during selected pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…The study was accepted by the Local Ethical Commission of the University of Warmia and Mazury in Olsztyn, Poland. The procedure of the experimental infection with B. hyodysenteriae as well as the sacrifice procedure were described elsewhere (Lakomy et al 2009). The infected animals were sacrificed when they developed strong, dysenteric diarrhoea with flecks of mucus, fragments of mucosa and blood.…”
Section: Methodsmentioning
confidence: 99%
“…We developed the experimental model using the domestic pig whose alimentary tract is the most similar to human one from the (patho)physiological point of view. The inflammation is induced by an experimental infection with Brachyspira hyodysenteriae, which induces necro-haemorrhagic inflammation of the colon called swine dysentery (Lakomy et al 2009). The model was successfully used to study various aspects of intestinal inflammation, however, we have found some discrepancies between the published results and the data obtained in the porcine model.…”
Section: Introductionmentioning
confidence: 99%